TOBACCO INDUSTRY LABOR MANAGEMENT COMMITTEE STATEMENT OF OPERATING CASH RECEIPTS AND DISBURSEMENTS AND OPERATING CASH BALANCE FOR THE YEAR ENDING 901231 (Tufts Archival Research Center, 2007)
Statement of cash receipts and disbursements from the Tobacco Industry Labor Management Committee for December 1990. Includes professional fees and contributions in support of other organizations.